Physicochemical Properties and Surface Characteristics of Ground Human Teeth - Katarzyna Sarna-Boś; Patrycja Boguta; Kamil Skic; Dariusz Wiącek; Paweł Maksymiuk; Jarosław Sobieszczański; Renata Chałas (Molecules, 2022)
Enamel, dentin and cementum apatite has a complex composition. The lack of complete reports on the chemical composition of all tooth tissues together and the need to create a modern biomaterial that reproduces the correct ratio of individual tooth mineral components prompted the authors to undertake the research. A detailed evaluation of the micro- and macro-elements of tooth powder, using various methods of chemical analysis was conducted. All four groups of human sound teeth were crushed using the grinder. A fine powder was implemented for the FTIR (Fourier Transform Infrared Spectroscopy), ICP (Inductively Coupled Plasma Optical Emission Spectometry) and for the potentiometric titration, SEM and mercury porosimetry analyses. The obtained studies indicate that there is no significant correlation in chemical composition between the different teeth types. This proves that every removed, crushed tooth free of microorganisms can be a suitable material for alveolar augmentation. It is essential to know the chemical profiles of different elements in teeth to develop a new class of biomaterials for clinical applications.